PERANCANGAN PRODUK FURNITUR INTERIOR DAN BOOTH DENGAN PENDEKATAN PRINSIP MINIMALIS OLEH NIW - Wijaya, Yehezkiel Nugraha Ivan; Nuradhi, Maureen; Rahadiyanti, Melania (Aksen : Journal of Design and Creative Industry, 2020)
The pace of the economy in Indonesia faces an era of shifting where many new businesses take advantage of this opportunity. The rapid growth of the Indonesian economy brings opportunities to various aspects of people’s lives, both from the pattern of the use of money to the opportunity to open a business. One of the contributors to Indonesia’s economic growth is the creative economy. Indonesia’s creative economy has become a promising new business opportunity, which is now also being cultivated by the community. The product and furniture industry is one of the 16 sectors of Indonesia’s creative economy. NIW an online or e-commerce based company has a share of the mass market where the company provides various needs for home furniture and interior accessories. The company carries a minimalist concept where the minimalist philosophy reflects an awareness of maximizing the consumption of goods by minimizing various components that are not needed. A minimalist visual form is expected to change the perspective and lifestyle of its users in between the complexities that often distract human thoughts and feelings in everyday life. Before the product is released to the market, the company makes a market reset so that the goods made can be accepted by the public. In addition to designing furniture, to support business activities a booth is needed as a media campaign. The booth on the NIW company is useful as a medium for exhibiting product results and is also a media space where prospective customers can feel, see, and feel directly for each product in order to understand and adjust the user’s tastes. The company collaborates with other creative industry personalities in various fields and several non competitor brands. Keywords: Collaboration, E-Commerce, Furniture, Minimalist, Product Design.